HUBUNGAN KINERJA KEUANGAN DENGAN RETURN SAHAM DIMODERASI OLEH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Kristianti Dewi, Luh; Sukartha, Putu D'yan Yaniartha (E-Jurnal Akuntansi; Vol 12 No 3 (2015), 2015)
The purpose of this study to determine the moderation disclosure of Corporate Social Responsibility on the relationship with the company 's financial performance of stock returns mining company in Indonesia Stock Exchange . Non - probability sampling technique with purposive sampling was used in the form of sampling . Purposive sampling technique is the determination of the sample with the criteria set by the researchers in some specific considerations with 56 sample . Documentation is used as a method of data collection and data analysis techniques using moderated regression analysis and residual . Terms of normality , autocorrelation and heteroscedasticity are covered by the research data .This study suggests the results of the interaction between financial performance variables ( X1 ) and CSR ( X2 ) indicates the disclosure of CSR is not able to strengthen the company 's financial performance relationship influences on stock returns
Keywords: financial performance , disclosure of CSR , the stock return